Pengaruh Quality Of Work Life (Qwl) dan Beban Kerja Terhadap Kepuasan Kerja Pegawai Pada Kantor Kesyahbandaran dan Otoritas Pelabuhan Kelas di Kijang - Intan Novita Sari; Myrna Sofia; Nurhasanah Nurhasanah (Bahtera Inovasi, 2018)
This study aims to determine and analyze whether there is influence of, quality of work life and workload to against employee job satisfaciton at Office X. This research is categorized as quantitative research with questionnaire instrument. Population in this research is all employees of Office X counted 41 people. Sampling technique by means of saturated sampling technique or census. The sample in this study is to take the population or as many as 41 samples. The data used in this study is the primary data obtained through Questionnaire. Instrument validity test using Correclation Bivariate formula, while reliability test using Cronbach Alpha. Measurers proved to be valid and reliable for research instruments. Multiple regression analysis is used to test the hypothesis of this research.Based on the results of this study it is known that the results of multiple linear regression test is Y = 2,826 + 0,16 X1 + 1,082 X2 where, quality of work life (X1), workload (X2 and job satisfaction (Y). Then T test results of variable quality of work life does not significantly affect employee job satisfaction (1,488 < 1,68288). Workload has a significant effect that is (22,009 > 1,6828. Test F together there is a significant influence on employee job satisfaction ( 247,626 > 2,85. R square test results give a value of 0,925 which mean 92,5% employee satisfaction variable can be explained through two independent variables, while the rest of 7,5% influenced or explained by other factors not included in this study.